The Sharia Business Model of The Housing Provident Fund (HPF) of Republic Of Indonesia - Ghoni, Muhammad Abdul; Amelia, Shinta Kintarani; Beyti, Nurul (EKOBIS SYARIAH, 2024)
This study introduces a sharia model of the HPF of republic of Indonesia. since, the Housing Provision Fund promotes housing investment and enables early house purchase for individuals with low income. The aim of this paper is presently sharia business model of provident fund and its implementing strategies to reduce the population of those needing adequate housing of Indonesian. This paper operates an extensive literature review explains the existing of housing provident fund model based on the sharia principle. The Sharia-compliant business model of the provident fund in the Republic of Indonesia is a relatively new mechanism that operates based on the principles of Shariah. It is designed to be fair and strives to achieve the ultimate goals of Sharia by establishing the Housing Provident Fund (HPF). The implementation of the Sharia business model in the housing provident fund of the Indonesian government can be replicated in other Muslim countries. As far as we know, this research is the first in the literature to present a conceptual idea and model for the sharia business model of housing provident fund that complies with Sharia principles.